Effects of the long-term aging of glass-fiber reinforced bearings (FRBs) on the seismic response of a base-isolated residential building. (15th October 2020) - Calabrese, A.; Losanno, D.; Barjani, A.; Spizzuoco, M.; Strano, S.
Highlights: Contribute towards shedding some light on the aging of FRBs. Contribute on the effect of aging on the performance of a typical residential building. A bilinear model has been adopted to describe the aging effects on the hysteretic response of FRBs. Nonlinear Response History Analyses have been performed on a benchmark structure. Abstract: Rubber based devices for seismic isolation have been adopted worldwide to protect buildings and bridges from seismic events. Very recently, a significant research effort has been dedicated to the study of Fiber Reinforced Bearings (FRBs), a low cost rubber based device for seismic hazard mitigation. In some applications, FRBs could be preferred over traditional steel reinforced isolators as: (i) they are lighter than conventional devices, (ii) FRBs can be produced with an easy manufacturing process where each bearing is cut to size and shape from a pad of large dimensions, (iii) FRBs require materials with low mechanical properties and cost. This is because FRBs are generally adopted in unbounded configurations and they are free to roll off from the supports. While these devices have shown to be an effective passive protection strategy in many applications, the effects of aging and other environmental conditions on the mechanical properties of these bearings are still to be addressed. With this consideration in mind, the aims of this work are those of: (i) studying the long-term performance and durability of FRBs through experimental testing, (ii) verifying the effects of aging on the response of FRBs both in compression and shear, (iii) determining the effects of aging of the bearings on the seismic response of a benchmark base isolated building, while (iv) comparing the as new and aged response of neoprene FRBs against that of conventional steel reinforced bearings. This work contributes toward determining the viability of FRBs as base isolation devices for residential buildings and toward determining the effects of their aging on the seismic response of a typical residential building.